Exercise: A Path to Wellness During Adjuvant Chemotherapy for Breast Cancer?. Issue 5 (September 2015) - Husebø, Anne Marie L.; Allan, Helen; Karlsen, Bjørg; Søreide, Jon Arne; Bru, Edvin
Abstract : Background: Breast cancer treatment can represent a threat to a patient's wellness. The role of exercise in perceived wellness in women with breast cancer merits further study. Objective: The objective of this study was to describe how exercise is perceived by women to influence their physical and psychosocial wellness at the time they were receiving chemotherapy. Methods: Five focus group interviews with a total of 27 women with early-stage breast cancer were conducted. Prior to the focus groups, the women had participated in an exercise intervention during chemotherapy treatment. Results: Three themes emerged from the analysis: exercise shapes feelings of psychological wellness; exercise stimulates feelings of physical wellness; and exercise influences social wellness. The women reported feeling stronger in a psychological sense after exercising, that the strength exercise improved their upper-limb functioning, and that engaging in exercise triggered social support and interactions. Conclusions: Exercise during breast cancer treatment is perceived to enhance the patients' wellness on several dimensions and in particular psychological wellness. Exercise might support the patients' efforts to restore their sense of wellness and enhance their level of daily life functioning. Implications for Practice: Cancer nurses should promote exercise as a wellness-fostering intervention during chemotherapy treatment. Focusing on how exercise can contribute to feelings of wellness may help women with breast cancer choose exercise as a health-promoting activity that contributes to their recovery.